Low Spatio-Temporal Frequency Wavefront Aberration Correction Method Based on a Movable Secondary Mirror - Yawei Xiao; Simin Zhao; Junbo Zhang; Linhai Huang; Naiting Gu (IEEE Photonics Journal, 2024)
A low frequency wavefront aberration correction method for solar telescopes based on secondary mirror movement is proposed to correct dynamic wavefront aberration during the operation of solar telescope. The correction ability of this method is analyzed and validated by numerical simulation and experiments. Theoretical analysis and numerical simulation both indicate the system processes significant aberration correction ability given the correction frequency of the secondary mirror movement is 10 times higher than aberration frequency. After spatiotemporal frequency division of actual wavefront data from solar telescope, the experiment result proves that the proposed correction method based on secondary mirror movement can effectively reduce the overall RMS of dynamic aberrations with high-frequency portion.